MDM2 RNA In Situ Hybridization for the Diagnosis of Atypical Lipomatous Tumor: A Study Evaluating DNA, RNA, and Protein Expression. (April 2019) - Kulkarni, Anupriya S.; Wojcik, John B.; Chougule, Abhijit; Arora, Kshitij; Chittampalli, Yashaswini; Kurzawa, Pawel; Mullen, John T.; Chebib, Ivan; Nielsen, G. Petur; Rivera, Miguel N.; Ting, David T.; Deshpande, Vikram
Abstract : The distinction of atypical lipomatous tumor/well-differentiated liposarcoma (ALT/WDL) from its benign counterpart, lipoma, may represent a challenge. MDM2 DNA amplification is used as the gold standard as MDM2 immunohistochemistry lacks specificity and sensitivity. Herein, we investigate the diagnostic utility of MDM2 RNA in situ hybridization (RNA-ISH) and compare the test with MDM2 immunohistochemistry and MDM2 DNA fluorescence in situ hybridization (FISH) in benign and malignant lipomatous neoplasms. We evaluated 109 neoplasms including 27 lipomas, 25 spindle cell lipomas, 32 ALTs/WDLs, and 25 dedifferentiated liposarcomas (DDL). The validation cohort included 14 lipoma-like neoplasms that lacked unequivocal features of ALT/WDL and in which MDM2 immunohistochemistry was either equivocal, negative or falsely positive. Immunohistochemistry, automated RNA-ISH and DNA-FISH for MDM2 were performed. Tumors with diffuse nuclear staining or >50 dots per cell on RNA-ISH were considered positive. All lipomas and lipoma variants were negative for RNA-ISH while all ALTs/WDLs and DDLs were positive. Eighty percent (24/30) and 92% (22/24) of ALTs/WDLs and DDLs were positive for MDM2 immunohistochemistry. Lipomas and its variants were negative for MDM2 amplification; 92% and 100% of ALTs/WDLs and DDLs showed MDM2 DNA amplification. The mean percentage of ALT/WDL tumor cells showing MDM2 RNA-ISH positivity was 73% compared with 24% on MDM2 immunohistochemistry. RNA-ISH correctly classified all 10 ALTs/WDLs and all 4 lipomas in the validation cohort. The performance of MDM2 RNA-ISH and MDM2 DNA-FISH are equivalent. MDM2 RNA-ISH can be of diagnostic value in histologically challenging lipomatous neoplasms. The automated MDM2 RNA-ISH assay should allow for more widespread use of MDM2 testing and for a more sensitive and specific diagnosis of ALT/WDL.